Fresno County Bar Association Law Day Luncheon: Attorney General John Van de Kamp - Watkins, Howard::::::::: (1987)
Fresno Mayor Dale Doig presenting to Fresno County Bar Association President Howard Watkins City Resolution designating May 1, 1987 Law Day in the City of Fresno; seated Carmen Romero and Sandra Snyder